Variation in the nominal morphology of Northern Vlax Romani. (March 2021) - Baló, Márton A.
Abstract : The present paper discusses two particular instances of variation in the nominal morphology of Northern Vlax Romani varieties as spoken in Hungary: the masculine oblique base and the feminine plural oblique base. The discussion is conducted in an analogical framework, relying only on surface forms and their relationships, using the notion of schemas (Booij 2010 ), and taking it one step further. When there is a 'weak point' in the grammar of a language, variation may emerge and pattern-seeking may begin; the pattern-seeking processes can be interpreted and explained with reference to possible analogical connections among surface forms.